1998
DOI: 10.1002/pro.5560070701
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of an engineered cro monomer bound nonspecifically to DNA: Possible implications for nonspecific binding by the wild‐type protein

Abstract: The structure has been determined at 3.0 8, resolution of a complex of engineered monomeric Cro repressor with a seven-base pair DNA fragment. Although the sequence of the DNA corresponds to the consensus half-operator that is recognized by each subunit of the wild-type Cro dimer, the complex that is formed in the crystals by the isolated monomer appears to correspond to a sequence-independent mode of association. The overall orientation of the protein relative to the DNA is markedly different from that observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…However, the few kinetic mechanisms determined to date revealed a richer picture, with parallel routes and transient intermediates (4)(5)(6)(7)(8). In the absence of high-resolution kinetic work, structural studies suggested that multistate routes for protein-DNA-binding start with the formation of nonspecific interactions with the DNA backbone (1,(9)(10)(11)(12)(13)(14)(15)(16)(17), and that some dual-role residues may form transient nonnative interactions along the route (13-15, 17). E2C-DNA-binding is also two-state at equilibrium (21) but kinetically complex (4) ( Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the few kinetic mechanisms determined to date revealed a richer picture, with parallel routes and transient intermediates (4)(5)(6)(7)(8). In the absence of high-resolution kinetic work, structural studies suggested that multistate routes for protein-DNA-binding start with the formation of nonspecific interactions with the DNA backbone (1,(9)(10)(11)(12)(13)(14)(15)(16)(17), and that some dual-role residues may form transient nonnative interactions along the route (13-15, 17). E2C-DNA-binding is also two-state at equilibrium (21) but kinetically complex (4) ( Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that proteins contact the DNA using approximately the same binding site and orientation in all complexes (10)(11)(12)(13)(14)(15)(16)(17)(18). In nonspecific complexes, the interface between the two molecules is stabilized by electrostatic interactions between charged protein side chains and the DNA backbone (1,(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 98%
See 3 more Smart Citations